Regulation of Mammalian Mitochondrial Gene Expression: Recent Advances. Issue 8 (August 2017) - Pearce, Sarah F.; Rebelo-Guiomar, Pedro; D'Souza, Aaron R.; Powell, Christopher A.; Van Haute, Lindsey; Minczuk, Michal
Abstract : Perturbation of mitochondrial DNA (mtDNA) gene expression can lead to human pathologies. Therefore, a greater appreciation of the basic mechanisms of mitochondrial gene expression is desirable to understand the pathophysiology of associated disorders. Although the purpose of the mitochondrial gene expression machinery is to provide only 13 proteins of the oxidative phosphorylation (OxPhos) system, recent studies have revealed its remarkable and unexpected complexity. We review here the latest breakthroughs in our understanding of the post-transcriptional processes of mitochondrial gene expression, focusing on advances in analyzing the mitochondrial epitranscriptome, the role of mitochondrial RNA granules (MRGs), the benefits of recently obtained structures of the mitochondrial ribosome, and the coordination of mitochondrial and cytosolic translation to orchestrate the biogenesis of OxPhos complexes. Trends: The genetic system required for mitochondrial gene expression is housed within the mitochondrial matrix, with all the necessary RNAs being provided by transcription of the mtDNA itself. Our understanding of the extent and nature of post-transcriptional modifications of mtRNA, the epitranscriptome, is rapidly expanding. Several required nucleus-encoded enzymes have recently been identified. mtRNA maturation factors localize in distinct foci, termed mtRNA granules, with newly transcribed RNA. These foci may allow spatiotemporal control of mtRNA processing. Recent high-resolution structures obtained via cryo-electron microscopy have rapidly advanced our understanding of the specialized adaptations of the mitochondrial ribosome. Production of respiratory complexes requires tight coordination between the cytoplasmic and mitochondrial translation systems.